PENGGUNAAN MEDIA KARTU HURUF DALAM MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS AWAL - Wilhelmina Menge; Efrida Ita; Andi Nafsia (CV. ADIBA ASIHA AMIRA, 2025)
This study aims to determine the utilization of letter card media in improving the reading skills of early grade students at Kekajodho Catholic Elementary School. This type of research is qualitative research. With the object of research is early grade students in class 1 totaling 15 people. With the methods used in this study, namely observation, interviews and documentation of student interest in reading, letter shape recognition, and combining letter sounds into words in supporting the improvement of reading skills of early grade students. The results showed that there was an increase in reading skills of early grade students where letter cards not only helped students recognize letters and combine sounds into words, but also created an interactive and fun learning atmosphere. Students were more engaged in learning, and they showed improved reading skills after the implementation of this method. This study provides important insights into the effectiveness of visual media in learning to read and its implications for teaching practices in the early grades. This study recommends the use of letter cards as learning media to improve students' reading skills, as well as the need for training for teachers in applying this method optimally.